Analysis on Part of Popular Learning Theory - Meezy Indriyansyah; Neviyarni Neviyarni; Herman Nirwana (Consilium, 2021)
Learning theory is a collection of general principles that are interrelated and explain a number of facts and findings related to learning events. Learning theory is one of the keys to the success of the learning process carried out by educators. In popular learning theory, there are several things that can be discussed, namely related to intelligent character education, quantum learning, accelerated learning, active learning and Hypno teaching. This popular learning theory has implications for effective and efficient learning.